Survival probability of road traffic injured cases in Thailand, 1996 - Podang, Jongkol
This study has two objectives, 1) to test accuracy of the TRISS model to predict survival probability of Thai traffic-injured cases and 2) to develop a new model to predict survival probability of road traffic injured cases. The data utilized were taken from the records of the Injury Surveillance System of the Ministry of Public Health operating in seven participant provincial hospitals during 1 January to December 31, 1996. The study subjects included those with severe injuries, 15 years old and above and with complete data on RTS, ISS, mechanism of injury, survival status and age. Data from study subjects who have complete physical indices *GCS, SBP and RR) were used to generate the new Revised Trauma Score. For cases with complete variables needed for TRISS model, the survival probability was computed. Likewise, the sensitivity and specificity of the TRISS model was calculated and then the number of actual and predicted survivors were compared using the Z statistic. The new model was developed using the multiple logistic regression. The accuracy of new survival probability model was compared with the original TRISS model.The results of this study showed that the TRISS model has high accuracy and sensitivity, 96, 99, respectively, but low specificity, 31. The Z statistic was significant because the number of actual survivors were less then number of survivors predicted by TRISS model (p-value0.05). The specificity of TRISS model is low. Since the distribution of characteristics which are associated with survival of the subjects from which the TRISS model was derived and traffic injured cases in Thailand were significantly different, TRISS model is not appropriate to predict survival from road traffic injuries of Thai cases.The new model developed to predict survival probability of severe blunt road traffic injury in Thailand contained the variables RTS, ISS and age with the new coefficients. The sensitivity and accuracy of the new model are comparable with TRISS model, while the specificity of the new model was higher. Thus the new model predicts survival probability better than TRISS model. It is recommended that the new model be applied in future injury cases in Thailand.
Thesis (Master of Science in Epidemilogy)--University of the Philippines Manila.
Keywords: Traffic injuries -- Survival rate. .; Road accidents. .